Indicators of the process of religiolization - Sagikyzy, A. (Chabaršy. Dintanu serijasy, 2022)
A variety of diverse factors and conditions have determined a complex process of religiousization. Its features in Kazakhstan are synchronized with the societal shifts of modernity. The substantive basis of the process is religiosity as an integral state of mental culture, which has various projections and determinations for individuals, social groups and society as a whole. The essence and dynamics of religiosity, its scale, vectors, and influences are presented as a process of religiousization and are the subject of research. Religiolization is not always an obvious phenomenon, and it requires the actualization of interdisciplinary capabilities (methodologies, methods, and practices) in specific socio-cultural country contexts. In order to identify the factors and indicators of religiousization, the manifestation of specificity, the detection of trends, and the analysis of trends, a factual basis of specific social dimensions is needed. These include monitoring the religious situation, the study of religious identification, assessment of the perception of the institution of religion, its role and functions, and analysis of the influence of significant political actors on the religious process. The analysis of social dimensions, theoretical reconstruction, and conceptualization by means of modern socio-humanitarian studies contribute to the institutionalization of the sociology of religion. The practical orientation is related to the understanding of the modern religious process as significant for the formation of the Kazakh mentality in the conditions of the postsecularity.